2016
DOI: 10.1021/acsenergylett.6b00403
|View full text |Cite
|
Sign up to set email alerts
|

Optical Resonance Engineering for Infrared Colloidal Quantum Dot Photovoltaics

Abstract: We report optically enhanced infrared-harvesting colloidal quantum dot solar cells based on integrated Fabry–Perot cavities. By integrating the active layer of the photovoltaic device between two reflective interfaces, we tune its sensitivity in the spectral region at 1100–1350 nm. The top and bottom electrodes also serve as mirrors, converting the device into an optical resonator. The front conductive mirror consists of a dielectric stack of SiN x and SiO2 with a terminal layer of ITO and ZnO in which curren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
42
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 32 publications
(43 citation statements)
references
References 34 publications
1
42
0
Order By: Relevance
“…The resulting reflection contributes to the device absorptance and introduces resonant absorption. This is due to interference between the forward-propagating light from the illuminated side and the backward-propagating light reflected on the gold electrode and can be controlled and optimized by adjusting the active layer thickness 13 , 32 . We thus measured the total absorption through complete PV devices (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The resulting reflection contributes to the device absorptance and introduces resonant absorption. This is due to interference between the forward-propagating light from the illuminated side and the backward-propagating light reflected on the gold electrode and can be controlled and optimized by adjusting the active layer thickness 13 , 32 . We thus measured the total absorption through complete PV devices (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In the last decade, intensive efforts have focused on improving CQD synthesis, surface passivation, film formation, and device engineering; and these have led to great strides in increasing the performance of CQD photovoltaics 6 12 . IR CQD solar cells, on the other hand, have remained comparatively underexplored, and best IR-filtered PCEs lie below 0.5% 4 , 13 , 14 .…”
Section: Introductionmentioning
confidence: 99%
“…Ouellette et al . 56 showed that by integrating the active layer of the photovoltaic device between two reflective interfaces the solar cells become sensitive for the spectral region at 1100–1350 nm, thus enabling effective IR light extraction. A schematic diagram of QDSWSC cartoon depicting the formation of WGM in SμS-TiO 2 and its effect in PCE along with the FESEM image of SμS-TiO 2 are given Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Lead chalcogenide narrow-bandgap colloidal quantum dots (CQDs) enable harvesting of infrared (IR) light in single-and multi-junction thin-film solar cells, since their bandgaps can readily be tuned across the solar spectrum by controlling nanocrystal size. [14][15][16][17][18][19][20][21] Advances in the surface chemistry of colloidal nanomaterials have enabled significant progress in the synthesis [22][23][24][25][26][27][28][29] and surface modification [30][31][32][33][34][35][36] of IR CQDs. Recently, lead halide-based solution-phase ligand exchanges on CQDs having a 1.3 eV (~950 nm) bandgap resulted in the highest-performing CQD solar cells to date, with certified power conversion efficiencies (PCEs) reaching 12% under simulated AM1.5 full solar illumination.…”
Section: Applications Their Size-and Facet-tunable Features Have Been Studied In Synthesis;mentioning
confidence: 99%